FUNGSI KOGNITIF MENENTUKAN KUALITAS HIDUP LANSIA - Latifah Susilowati; Umi Istianah (MEDIA ILMU KESEHATAN, 2012)
Introduction: Elderly will experience the aging process that affects the change in physical condition,function, psychosocial aspects, and social roles. One of functional changes in the elderly is a change incognitive function. Decreased cognitive function is one of the factors that can affect the lives of the elderly, especially the quality of their lives. The objective of this study was to determine the relationship between cognitive function and quality of life in elderly in the Hamlet of Gamping Kidul. This study provides information and an ove rview of cognitively impaired elderly in various levels and their quality oflife. Methods: This study was an observational research with a cross sectional design. The number of samples was 107 elderly people who fit the criteria of inclusion and exclusion. Measurement of cognitive function used an instrument of MMSE (Mini Mental State Examination) and measurement of quality of life used the instrument of CBS (Cornell Brown Scale). Statistical test used Spearman Rho correlation test. Results: Based on the results of the study, 94 respondents (87.9%) had no cognitive impairment, 11 respondents (10.3%) had mild cognitive impairment, and 2 respondents (1.8%) had severe cognitiveimpairment. Spearman Rho correlation test results showed a p value of 0.000 (p<0.05). Significan cevalues showed a significant correlation between cognitive functionand quality of life. Conclusion: There was a significant relationship between cognitive function and quality of life of elderly people in the Hamlet of Gamping Kidul, Sleman, Yogyakarta. It is suggested that appropriate activities should be held to maintain cognitive function in the elderly. Keywords: Elderly, cognitive function, quality of life